New policy challenges for European multinationals - Tulder, Rob van; Verbeke, Alain; Voinea, Liviu (Emerald, 2012)
This volume takes stock of the latest international business research on the relationship between European multinational enterprises (MNEs) and their policy environment. The volume brings together a variety of scholarly contributions from an European perspective. European MNEs were amongst the earliest to internationalize and many now command globally dispersed operations. European MNEs pioneered the multi-centric organizational form, which can be interpreted in part as an effort to address the policy challenges facing these firms in environments fraught with natural and government-imposed market imperfections. The volume covers four dimensions of MNE corporate strategy in the face of complex policy environments: 1. Corporate strategic responses to national policy institutions 2. Pro-active institution-oriented strategies 3. Dynamics of international business-government relations; 4. Corporate strategies in turbulent times.
Keywords: International business enterprises -- Europe.; Business planning -- Europe.; International business enterprises -- Law and legislation -- Europe.; elektronické knihy; electronic books